Enzymatic Browning Potential of “Nopalitos” Varieties - Aguilar-Sánchez, Laura; Martínez-Damián, Ma. Teresa; Barrientos-Priego, Alejandro F.; Aguilar-Gallegos, Norman; Gallegos-Vásquez, Clemente (Journal of the Professional Association for Cactus Development, 2007)
In Mexico, there is a tradition in the cultivation and use of young cactus cladodes as a vegetable named “nopalitos”. However, the presentation form for its commercialization (minimally processed) is one of the main problems that this product has. Enzymatic browning caused by the enzyme polyphenoloxidase (PPO) becomes one of the problems during processing and conservation. Because very few studies exist that include postharvest physiology of nopalitos, the present research had the aim to evaluate some physical and biochemical characteristics of 21 varieties of Opuntia, as well as to determine the activity of the enzyme polyphenoloxidase (PPO) and its browning potential. Evaluated variables were: weight, length, width, color (L, hue, croma), pH, chlorophyll content, total soluble solids content, and the activity of PPO with the purpose of knowing their browning potential. Significant differences were found among the analyzed varieties. outstanding ‘Chicomostoc’, ‘Negrito’ and ‘Jade’ are the most capable varieties for minimal processing and whose attributes in postharvest are the most desirable due to their low browning potential, surpassing ‘Milpa Alta’ which is the most cultivated and marketed variety in Mexico.